Prototipe Sistem Deteksi dan Monitoring Penurunan Muka Tanah Pada Lahan Pertanian Gambut Berbasis IoT - Aulia Fitri; Yulisa Suryana; Ade Putri Maharani; Elisa Fitriana; Ihsanudin; Rudy Ansari; Finki Dona Marleny (TEMATIK, 2023)
Agriculture on peatlands has great potential to meet food and economic needs but also requires attention to sustainable management. Agriculture on peatlands faces several serious challenges. Peatlands tend to be fragile, with risks of subsidence, fire, and degradation. To overcome the problem of land subsidence in peatland agriculture, action, integration from various parties, and proper monitoring are needed. IoT systems integrated with soil level monitoring can help minimize peatland destruction and improve agricultural sustainability. From the problem of land subsidence in peat farmland, a solution to monitor land subsidence is proposed as a prototype system to detect and monitor land subsidence on peat agricultural land. This system uses an integrated sensor system designed on Arduino and integrated with the web to facilitate the monitoring process. The prototype is designed according to the characteristics of peat farmland. The results obtained from this prototype can vary depending on the complexity of the system and the data collected, from the results of trials and simulations carried out by this system prototype can be an alternative in increasing the productivity and sustainability of peatland while reducing the risk of environmental damage. In the long term, these results can also have a positive impact on agricultural sustainability and peatland sustainability.